Peningkatan Efikasi Diri Melalui Edukasi Kesehatan Terstruktur pada Pasien Tuberkulosis Paru - Kausar, Lola Illona Elfani; Nursasi, Astuti Yuni; Fitriyani, Poppy (FORIKES, 2023)
Clients with pulmonary tuberculosis experience physical, psychological, social, and spiritual changes that can have an impact on decreasing self-efficacy, so that they tend to stop treatment and as a result can become agents of transmission. This study aimed to analyze the effectiveness of structured health education to improve the self-efficacy of clients with pulmonary tuberculosis. This study was a quasi-experimental study with a pretest-posttest with control group design, which was conducted in 2 health centers in Murung Raya Regency. This study involved 76 clients with tuberculosis recruited using a cluster sampling technique, which were then divided into 2 groups. The treatment group was given structured health education for 4 times 60-120 minutes (4 sessions) in four weeks. In the pre- and post-intervention phases, self-efficacy measurements were carried out using a questionnaire. Furthermore, data analysis was carried out using the t-test. The results of the paired samples t-test showed a p-value of 0.001 (there was a difference in self-efficacy between before and after the intervention) for the treatment group and 0.694 (there was a difference in self-efficacy between before and after the intervention) for the control group. The results of the independent samples t-test for the difference in self-efficacy between the two groups in the post-intervention phase showed a p-value of 0.001, which means there was a difference in self-efficacy between the two groups. Based on the results of the analysis, it could be concluded that structured health education is effective in increasing the self-efficacy of clients with pulmonary tuberculosis.Keywords: pulmonary tuberculosis; self-efficacy; structured health education ABSTRAK Klien dengan tuberkulosis paru mengalami perubahan fisik, psikologis, sosial, dan spiritual yang bisa berdampak pada penurunan efikasi diri, sehingga cenderung akan menghentikan pengobatan dan akibatnya dapat menjadi agen penularan. Penelitian ini bertujuan untuk menganalisis efektifitas edukasi kesehatan terstruktur untuk meningkatkan efikasi diri klien dengan tuberkulosis paru. Penelitian ini merupakan studi eksperimental kuasi dengan rancangan pretest-posttest with control group, yang dilaksanakan di 2 puskesmas di Kabupaten Murung Raya. Studi ini melibatkan 76 klien dengan tuberkulosis yang direkrut dengan teknik cluster sampling, yang selanjutnya terbagi dalam 2 kelompok. Kelompok perlakuan diberi edukasi kesehatan terstruktur selama 4 kali 60-120 menit (4 sesi) dalam empat minggu. Pada fase sebelum dan sesudah intervensi dilakukan pengukuran efikasi diri menggunakan kuesioner. Selanjutnya dilakukan analisis data menggunakan uji t. Hasil paired samples t-test menunjukkan nilai p adalah 0,001 (ada perbedaan efikasi diri antara sebelum dan sesudah intervensi) untuk kelompok perlakuan dan 0,694 (ada perbedaan efikasi diri antara sebelum dan sesudah intervensi) untuk kelompok kontrol. Hasil independent samples t-test untuk perbedaan efikasi diri antara kedua kelompok pada fase sesudah intervensi menunjukkan nilai p adalah 0,001, yang berarti ada perbedaan efikasi diri antara kedua kelompok. Berdasarkan hasil analisis tersebut dapat disimpulkan bahwa edukasi kesehatan terstruktur efektif untuk meningkatkan efikasi diri klien dengan tuberkulosis paru.Kata kunci: tuberkulosis paru; efikasi diri; edukasi kesehatan terstruktur